Hadith Scholarship in Baghdad and Andalusia (2nd–5th Centuries): A Comparative Study of al-Riḥlah, Intellectual Networks, and Textual Canonization - Wibowo, Rahmadi; bin Soroni, Mohd Khafidz; binti Wazir, Rosni; Kholis, Nur (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Baghdad held a strategic position as a center of intellectual brilliance and Islamic civilization, while Andalusia emerged as one of the most advanced Islamic civilizations under the Umayyad dynasty. This comparative study is crucial for understanding how scholarly networks influenced the development of hadith scholarship and the respective contributions of these regions, given the scarcity of systematic comparative studies on hadith studies in these specific areas, particularly between Baghdad and Andalusia. Employing a qualitative method with historical and comparative analysis, this research aims to examine the characteristics and comparisons of three key aspects: al-riḥlah, teacher-student networks, and written works before the 5th century Hijri. The findings reveal that scholars in Baghdad undertook al-riḥlah to Mecca, Medina, Kufa, Basra, Syam, Yemen, Maghreb, Khurasan, and Samarkand to obtain elevated chains of transmission (‘ulūw al-isnād) and leveraged the city’s central position as an intellectual hub. In contrast, Andalusian scholars conducted expansive al-riḥlah to the Levant, the Hijaz, Baghdad, and Egypt to strengthen their sanad and collect hadith manuscripts. The scholarly network in Baghdad exhibited dynamic mazhab interactions, whereas in Andalusia, it was hierarchical-territorial and predominantly centered around Maliki scholars such as Yaḥyā al-Laythī. Written contributions in Baghdad produced diverse genres, primarily dominated by kitāb al-rijāl and al-musnad, while Andalusian works focused extensively on syarah and transmission pathways of al-Muwaṭṭa’, establishing a dominant trend.